Exosome and virus infection - Peng, Yiqiu; Yang, Yuxi; Li, Yingying; Shi, Tingjuan; Luan, Yingyi; Yin, Chenghong (Frontiers in Immunology, 2023)
Exosomes are messengers of intercellular communication in monolayer vesicles derived from cells. It affects the pathophysiological process of the body in various diseases, such as tumors, inflammation, and infection. It has been confirmed that exosomes are similar to viruses in biogenesis, and exosome cargo is widely involved in many viruses’ replication, transmission, and infection. Simultaneously, virus-associated exosomes can promote immune escape and activate the antiviral immune response of the body, which bidirectionally modulates the immune response. This review focuses on the role of exosomes in HIV, HBV, HCV, and SARS-CoV-2 infection and explores the prospects of exosome development. These insights may be translated into therapeutic measures for viral infections and reduce the disease burden.